PEMBELAJARAN BERBASIS SENTRA DALAM MENGEMBANGKAN KEMAMPUAN MOTORIK ANAK USIA DINI - Suhirman; Rayani Fitri (Al-Thifl: Jurnal Pendidikan Anak Usia Dini, 2005)
Early childhood is a golden period in which the stimulation of motor skills, both gross and fine motor, plays a decisive role in supporting children's overall growth and development. Center-based learning, known in Indonesia as Beyond Centers and Circle Time (BCCT), is a model believed to be effective in stimulating children's motor development because it places children as active subjects who explore various play centers under the teacher's scaffolding. This article examines how center-based learning is implemented to develop the motor skills of early childhood, identifies the supporting and inhibiting factors of its implementation, and describes its contribution to children's gross and fine motor development. A qualitative literature review (library research) method was used, collecting, analyzing, and synthesizing relevant books, national and international journal articles, and government regulations related to center-based learning and early childhood motor development. The results show that centers such as the block center, natural materials center, preparation center, art center, and role-play/body-movement center provide children with authentic and varied play experiences that stimulate large-muscle movement (gross motor) as well as fine hand-eye coordination (fine motor). The consistent application of the four types of scaffolding, namely environmental, before-play, during-play, and after-play scaffolding, is a key factor for success. The article concludes that center-based learning is an effective alternative model for optimally developing early childhood motor skills when implemented consistently, supported by adequate facilities, and carried out by competent educators.